2024
DOI: 10.1002/anie.202318505
|View full text |Cite
|
Sign up to set email alerts
|

Depicting the Chemical Diversity of Bioactive Meroterpenoids Produced by the Largest Organism on Earth

Sebastian Pfütze,
Esteban Charria‐Girón,
Esther Schulzke
et al.

Abstract: In this investigation, we explored the diversity of melleolide‐type meroterpenoids produced by Armillaria ostoyae, one of the largest and oldest organisms on Earth, using extracts from liquid and solid fermentation media. The study unveiled three unprecedented dimeric bismelleolides (1‐3) and three novel fatty acid‐substituted congeners (4‐6), along with 11 new (7‐17) and 21 known (18‐38) derivatives. Structure elucidation was done by 1D‐ and 2D‐NMR spectroscopy, HRESI‐MS data, and ROESY spectral analysis for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…For this purpose, it might even be feasible to use modern metabolomics techniques as recently employed for a strain of the basidiomycete Armillaria. Polyphilus spp., however, should perhaps not be further pursued with priority for biocontrol purposes because several of the metabolites we have encountered may be potentially harmful for beneficial organisms, and even the production of the marketed antibiotic drugs of the fusidic acid type, which were finally identified as major antibacterial principles, may pose a risk that can lead to antimicrobial resistance against the antibiotic among soil bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, it might even be feasible to use modern metabolomics techniques as recently employed for a strain of the basidiomycete Armillaria. Polyphilus spp., however, should perhaps not be further pursued with priority for biocontrol purposes because several of the metabolites we have encountered may be potentially harmful for beneficial organisms, and even the production of the marketed antibiotic drugs of the fusidic acid type, which were finally identified as major antibacterial principles, may pose a risk that can lead to antimicrobial resistance against the antibiotic among soil bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…[6] Our recent case study on A. ostoyae has revealed that a single strain can produce over 40 different derivatives of this type. [7] Desarmillaria, a genus containing species that are morphologically similar to those of Armillaria, was segregated from the latter genus by Herink (1973) based on comparative morphol-ogy. It has recently been confirmed that this segregation was valid based on polyphasic taxonomy including multi-locus phylogenetic studies.…”
Section: Introductionmentioning
confidence: 99%